Testing: Academic &Amp; Industrial Conference - Practice and Research Techniques (Taic Part 2008) 2008
DOI: 10.1109/taic-part.2008.20
|View full text |Cite
|
Sign up to set email alerts
|

Feedback-Based Specification, Coding and Testing with JWalk

Abstract: JWalk is a lazy systematic unit-testing tool for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Our previous experiments have shown that trying to achieve similar complete test coverage by manual test case selection will yield much poorer results [2,21]. The JWalk tools take control of the selection of test cases, here guided by algebraic analysis, relieving the tester of this burden.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous experiments have shown that trying to achieve similar complete test coverage by manual test case selection will yield much poorer results [2,21]. The JWalk tools take control of the selection of test cases, here guided by algebraic analysis, relieving the tester of this burden.…”
Section: Discussionmentioning
confidence: 99%
“…Specification-based testing methods seek to validate the software unit completely against a formal specification, which serves as a test oracle. Recently, these approaches have started to converge, particularly in the lazy systematic unit testing method [1,2], which combines semi-automatic inference of the test unit's specification with systematic conformance testing from the specification. The power of this method depends critically on an automated dynamic analysis to identify the most important test cases, whose outcomes must be confirmed by the tester.…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations